SOME ASPECT OF PUBLIC UTILITY ACCOUNTING. - Avery, Harold G. (The Accounting Review, 1954)
Abstract The article focuses on public accounting. The contention that generally accepted accounting principles are recognized and applied by public utilities is supported, although the utility industry must maintain a uniform system of accounts as prescribed by state and federal regulatory commissions. The field of public utilities consists of electric light and power; gas and steam heating, telephone, telegraph, and others. This utility from hereon will be referred to as the Company. The Company classifies its accounts in accordance with the prescribed system of accounts issued by the public service commissions. It files with the commission a copy of its manual of accounts and any changes that are made in the account classification. Certain account classifications are established to facilitate the allocation of costs. These classifications include the accrued and deferred accounts, work in progress, joint expenses and clearing accounts. Clearing accounts contain the accumulation of costs under similar account titles during the fiscal period, the amounts of which are transferred currently to the particular permanent account on some predetermined cost distribution basis.